LABORATORY ISSUES IN THE DIAGNOSIS OF MALE INFERTILITY (World Bulletin of Public Health, 2025)
Laboratory diagnostics of male infertility are primarily developing in the morphological direction. However, spermogram results may be prone to subjective errors and variability. While biochemical tests are stable, they are not adapted for working with spermatozoa. Male infertility arises under the influence of various factors, including social, ecological, and demographic, which complicates diagnosis. Therefore, new approaches are necessary for identifying disorders of spermatogenesis, such as reduced sperm count, decreased motility, or increased pathological forms. Research, particularly focused on developing and validating biomarker-based methods, is ongoing. The identification of biomarkers, analysis of genetic and epigenetic changes, microbiota, and the use of automated systems for analysis can improve diagnostic accuracy. Innovative approaches will enable more precise infertility diagnosis and allow for more individualized treatment methods.
Keywords: Male infertility; laboratory diagnostics; spermogram